An Audit of Indications, Complications, Correlation of Preoperative Diagnosis with the Histopathology Report of Hysterectomies at Shalamar Hospital Lahore - Binyamin Butt, Mahwish Saif, Sadia Mustafa, Maryam Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Hysterectomy is the most common gynecological procedure. Abdominal approach is preferred for an enlarged uterus especially in cases of fibroids. However, in a small sized uterus, use of vaginal route is supported in well selected cases Objective: Aim of this audit was to analyze indications, complications, and correlation of preoperative diagnosis with the histopathology report for all hysterectomies, performed in a Shalamar Hospital Lahore. Methods: This study was crass sectional and population the obs. And Gyn. Patients of Shalamar Hospital Lahore. This study is a three year retrospective review of 755 cases of hysterectomy either for gynecological or obstetric reasons managed at Shalamar Hospital Lahore from January 2019 to December 2021. Results: Abdominal hysterectomy accounted for 94%, while vaginal hysterectomy accounted for the remaining 6%. In the former category, an 86% had total abdominal hysterectomy while 9% had subtotal hysterectomy. The average duration of hospital stay following surgery was 3-5 days. The average indoor stay was 2-3 days after vaginal hysterectomy and 4-5days after abdominal hysterectomy. There were 4 cases of mortality accounting for a mortality rate of 1.8 %. Post operative morbidity was encountered in 29.4% of the patients. Anaemia was observed in 45.9%,post operative wound infection in 30.1%, pyrexia in 9% patients, chest infection in 6.7%, bladder injury in 3.6%, bowel injury in 1.8% of the patients. Practical Implication: The practical implication of this study is to correctly treat the patients with pre-operative investigation, Complications, and Correlation of Preoperative Diagnosis with the Histopathology Report of Hysterectomies in private hospitals. Conclusions: Hysterectomy is a major gynaecological procedure. Selection of a appropriate route is very important for the safety of the patient and for hospital stay. Like any other surgery, hysterectomy has an inherent set of complications. So clinical selection should be well justified. Like in any major gynecological procedure, a skilled operator can reduce the morbidity and mortality rates. The conservative approaches should be offered before opting for hysterectomy. Keywords: Pre-operative investigation, Hysterectomies, complications, private hospital, Obs and Gyn patients